If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 2) + -1(-7y + -3) = -6 Reorder the terms: -1(2 + 8y) + -1(-7y + -3) = -6 (2 * -1 + 8y * -1) + -1(-7y + -3) = -6 (-2 + -8y) + -1(-7y + -3) = -6 Reorder the terms: -2 + -8y + -1(-3 + -7y) = -6 -2 + -8y + (-3 * -1 + -7y * -1) = -6 -2 + -8y + (3 + 7y) = -6 Reorder the terms: -2 + 3 + -8y + 7y = -6 Combine like terms: -2 + 3 = 1 1 + -8y + 7y = -6 Combine like terms: -8y + 7y = -1y 1 + -1y = -6 Solving 1 + -1y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = -6 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = -6 + -1 -1y = -6 + -1 Combine like terms: -6 + -1 = -7 -1y = -7 Divide each side by '-1'. y = 7 Simplifying y = 7
| x-y/4 | | x^2=3(2x-3) | | 3x^2-2y-8=0 | | -x-5y=15 | | 6(4x-3)=2(12x+9) | | 6+4t-2=7t+12-2t | | x^2/70 | | 3/2ln(16x^2)-2/5ln(2y^25) | | 9x+3=5-(5x-5) | | (x^2+x-5)= | | 6x-y=-32 | | 5h=t-5u | | -x^4-4x^2-16=0 | | t-5u=5h | | 9y+7y=96 | | -x^4+4x^2+16=0 | | (-9x+1)= | | (-9x+1)+(x^2+x-5)= | | 3-7(8-5x)=0 | | 4-6(7x+2)=9 | | (8/17)/(3/5) | | (5/8)*16 | | 8+6m-3=9m+9-2m | | (7/9)-(1/6) | | 5v^2+5=-26v | | -x^2-10x-20=0 | | (2/7)+(1/12) | | -5x-4y=-33 | | (x+5)/(3x+1) | | 5.7q-4.7-5.9q=-1.2q-1.8 | | 3u^2-5u=2 | | -3y+1=-4y+7 |